Sinus procedures in the Medicare population from 2000 to 2014: A recent balloon sinuplasty explosion. (11th April 2017) - Calixto, Nathaniel E.; Gregg‐Jaymes, Twyla; Liang, Jonathan; Jiang, Nancy
Abstract : Objective: To describe sinus procedure trends from 2000 to 2014, particularly following the introduction of balloon sinuplasty Common Procedural Technology (CPT) codes in 2011. Study Design: Retrospective review of Medicare billing data available to the public. Methods: Procedure and beneficiary data from 2000 to 2014 and provider data from 2012 to 2014 were obtained online from the Centers for Medicare and Medicaid Services. Sinus CPT codes were classified as balloon sinus procedure (BSP) or nonballoon sinus procedure (nBSP). Providers billing for sinus procedures were categorized as BSP only, nBSP only, or both. For comparison, data on septoplasty procedures from 2000 to 2014 were obtained. Results: From 2000 to 2014, the total number of sinus procedures per 10 thousand beneficiaries (PP10K) nationwide increased by 3.7% annually. From 2011 to 2014, nBSP PP10K decreased by 3.1% annually, and BSP PP10K increased by 59% annually. Septoplasty PP10K changed by < 1% annually between 2000 and 2014. States with the highest BSP PP10K from 2012 to 2014 were Kansas, Texas, and Louisiana. Providers performing sinus procedures increased by 30.9% from 2012 to 2014. There was a 244% increase in BSP‐only providers, a 0.7% increase in nBSP‐only providers, and an 83.3% increase in providers using both. Septoplasty providers increased by 4.1%. Conclusion: Although the total number of sinus procedures increased from 2000 to 2014, the number of BSP increased at a substantially greater rate since the introduction of CPT codes for these procedures in 2011. Nationwide increases in sinus providers were driven by new providers performing balloon‐guided procedures. Level of Evidence: 4. Laryngoscope, 127:1976–1982, 2017